Structure and Dominance of Species in Mangrove Forest on Kutai National Park, East Kalimantan, Indonesia - Muli Edwin; Iin Sumbada Sulistyorini; Erny Poedjirahajoe; Lies Rahayu Wijayanti Faida; Ris Hadi Purwanto; Imanuddin; Muli Edwin, Muli (Jurnal Manajemen Hutan Tropika, 2021)
The Kutai National Park (KNP) which is located in East Kutai Regency on East Kalimantan Province is endowed with numerous pristine of mangrove forest. However, related information to the species composition and diversity of KNP mangrove is still scanty. Twenty-one of mangrove species were recorded using the quadratic transects survey method (total plot area of 1.7 ha). Main species of mangrove communities were Avicennia lanata, A. marina, Bruguiera gymnorrhysa, B sexangular, Ceriops tagal, Rhizophora apiculata, R. mucronata and Sonneratia Alba. Mangrove density was recorded reached as 1,699 trees ha-1, saplings of 4,395 ha-1 and seedlings 25,348 ha-1. Significant tree density was found in Pandan Bay Estuary. While in the Lombok Bay and the Kaba Bay significant for sapling and seedling categories. Importance value index of mangrove species in the three study locations for three growth categories (tree, sapling and seedling) showed significant differences (p-value> α0.05). Mangrove stand at three study locations has almost the same characteristics. The species diversity and evenness index has shown the same distribution pattern. The findings of this study suggest that KNP mangrove forest stand is not heavily damaged even though there is a lot of human activity. This mangrove could be managed and conserved for multi-sectoral purposes such as ecotourism, research, biodiversity and education rather than solely as a Nature Conservation Area.